2010
DOI: 10.1074/jbc.m110.123984
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Control of Internal Electron Transfer in Bacterial Nitric-oxide Reductase

Abstract: Nitric -oxide reductase (NOR) fromconcomitantly with oxidation of the low spin hemes, leading to an acceleration at low pH. This effect is, however, counteracted by a larger degree of substrate inhibition at low pH. Our data thus show that substrate inhibition in NOR, previously observed during multiple turnovers, already occurs during a single oxidative cycle. Thus, NO must bind to its inhibitory site before electrons redistribute to the active site. The further implications of our data for the mechanism of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
40
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 35 publications
16
40
1
Order By: Relevance
“…Without further kinetic data, we cannot exclude that at a later mechanistic step heme b 3 will somehow bind to NO (or to a reaction intermediate). Recently, Lachmann and coworkers (52) demonstrated that CO binds to reduced heme b 3 (probably displacing the sixth ligand initially present) and that flash-induced dissociation causes heme b 3 oxidation and catalysis. It is also known that for the CO-bound enzyme, NO can still bind to the Fe B site (14).…”
Section: Discussionmentioning
confidence: 99%
“…Without further kinetic data, we cannot exclude that at a later mechanistic step heme b 3 will somehow bind to NO (or to a reaction intermediate). Recently, Lachmann and coworkers (52) demonstrated that CO binds to reduced heme b 3 (probably displacing the sixth ligand initially present) and that flash-induced dissociation causes heme b 3 oxidation and catalysis. It is also known that for the CO-bound enzyme, NO can still bind to the Fe B site (14).…”
Section: Discussionmentioning
confidence: 99%
“… and Ref. on a set‐up custom built by Applied Photophysics (Leatherhead, UK). Briefly, samples of ~ 5 μ m c NOR (in 50 m m HEPES, pH 7.5, 50 m m KCl, 0.05% DDM, 0.2 μ m PMS, 30 m m glucose, 20 U·mL −1 catalase) were prepared in modified Thunberg cuvette.…”
Section: Methodsmentioning
confidence: 99%
“…73 s −1 [37]). Lachmann and co-workers [39] used spectroscopic methods to determined re-oxidation rate constants of the NOR metal co-factors under NO turnover, however, the determined values present substrate concentration dependence and are lower (c.a. 12 s −1 [39]) than the ones determined for the direct ET between the enzyme and the graphite electrode [37].…”
Section: The No Inhibitory Profilementioning
confidence: 97%
“…This hypothesis was strongly supported by the stability of heme Fe III -nitrosyl compounds [11]. Lachmann and co-workers used flow-flash measurements in single turnover conditions demonstrating that substrate concentration controlled the intramolecular electron transfer (ET) in the NO reduction mechanism and the substrate binding to the inhibition site occurs before the electron redistribution to the catalytic centre [39]. Recently, a theoretical study developed with DFT calculations has indicated a weak interaction between NO and the oxidised binuclear iron centre, suggesting an inhibitory profile caused by nitrate formation from a side reaction [28].…”
Section: Introductionmentioning
confidence: 93%